Zion-French Relations 1948 – 1973 (Journal of the College of Basic Education, 2022)
The totality of developments in the European continent since the eighteenth century led to a tangible change in the conditions of the Jews. The French Revolution made way for the completion of the results of the economic and social development of the Jews. Hence, the timing of the birth of the Zionist movement in the era of the transformation of capitalist regimes to the stage of monopoly and the search for The areas of influence outside the European continent and the complete compatibility between the plans of Zionist imperialism in the regions of the Arab East.From here, the Zionist movement realized, since its inception, to establish a homeland in Palestine, and this goal can only be achieved with the help of the great powers. France was among the first European countries that the Zionists sought to ally with. Despite the Zionists, at the beginning of achieving their goals, they focused on working with Britain by virtue of the growth of capitalism and its expansion outside its borders. Its need for funds to establish colonies was owned by the Jews simultaneously with the influence of the Zionists on its lands, but this did not prevent the French from launching a campaign against Egypt and the Levant in 1798 in preparation for the return of the Jews to Palestine. France had a major role in establishing a short entity in Palestine.The aim of the research is to trace the Zionist-French relations from 1948-1973, a period full of political developments and facilities provided by the French to the Zionists. The French colonialism also opened opportunities for the Zionists to go to Africa as experts, technicians, and businessmen. As a result, the Zionists opened honorary consulates in some countries, which later turned into After the independence stage to embassies there.The importance of the research lies in that it sheds light on a vital topic that researchers did not address properly, and no independent research has emerged on the relationship of the Zionist entity with the great powers that France stands at its head, or on the economic relationship of the Zionists, of which France is one of its main pillars.